SELF-RESTITUTION DAN MOTIVATIONAL INTERVIEWING UNTUK MENGADVOKASI PESERTA DIDIK KORBAN KEKERASAN SEKSUAL ONLINE: PRAKTIK BAIK GURU PENDIDIKAN AGAMA ISLAM DAN KONSELOR SEKOLAH - Mochammad Zaka Ardiansyah; Faradys Basmalah Alfaqod; Hoiriah Agustin Mega Wulandari; Moh. Ardiyansyah (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
This article reports on advocacy by Islamic Religious Education teachers and counselors for student who are victims of online sexual violence in secondary schools. The author conducted interviews with an Islamic Religious Education teacher and a Guidance and Counseling teacher, both at school and at their homes, to explore their advocacy efforts for such student in a case study. The article found that Islamic Religious Education teacher used self-restitution, while Guidance and Counseling teacher applied motivational interviewing technique. The author recommends that professional counselors in schools enhance their religious and spiritual skills for stronger school-based counseling interventions. In addition, by implementing the Love-Based Curriculum, Islamic Religious Education teachers can help students internalize the value of love for others, prevent online sexual violence, and participate with Guidance and Counseling teachers in supporting trauma recovery for student victims.